2016
DOI: 10.1016/j.cattod.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic behavior of precisely synthesized Pt–Pd bimetallic catalysts for use as diesel oxidation catalysts

Abstract: The demands of stricter diesel engine emission regulations have created challenges for current exhaust systems. With advances in low-temperature internal combustion engines and their operations, advances must also be made in vehicle exhaust catalysts. Most current diesel oxidation catalysts use heavy amounts of precious group metals (PGMs) for hydrocarbon (HC), CO, and NO oxidation. These catalysts are expensive and are most often synthesized with poor bimetallic interaction and dispersion. The goal of this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In this context, continuous catalyst improvement by combining different catalytically active materials are an essential aspect of environmental research and can substantially improve heterogeneous catalysts [24]. Although palladium shows only minor NO oxidation activity, its combination with platinum can serve as an effective measure to minimize deactivation phenomena for diesel oxidation catalysts [25][26][27][28][29]. Moreover, palladium shows higher thermal stability under oxidizing conditions compared to oxidized platinum, as the latter one forms volatile PtO2; hence, the usage of a Pt-Pd alloy has been reported as an efficient approach to increase the catalyst's thermal stability [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, continuous catalyst improvement by combining different catalytically active materials are an essential aspect of environmental research and can substantially improve heterogeneous catalysts [24]. Although palladium shows only minor NO oxidation activity, its combination with platinum can serve as an effective measure to minimize deactivation phenomena for diesel oxidation catalysts [25][26][27][28][29]. Moreover, palladium shows higher thermal stability under oxidizing conditions compared to oxidized platinum, as the latter one forms volatile PtO2; hence, the usage of a Pt-Pd alloy has been reported as an efficient approach to increase the catalyst's thermal stability [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Carrillo et al [38] reported that PdO nanoparticles can trap mobile Pt species under oxidizing conditions, which is of high relevance for understanding the behavior of bimetallic Pt-Pd catalysts. Lately, a wide variety of advanced materials has been proposed for catalytic emission control under lean conditions, namely encapsulated coreshell catalysts [25,39,40] and nanostructured architectures [41,42] for oxidation reactions and microporous materials for NOx control [43][44][45][46]. Although these materials often show extremely promising catalytic activity or stability, fundamental in-depth understanding, transfer into industrial application and upscaling of preparation procedures remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Even though a typical diesel exhaust contains a variety of 173 hydrocarbon components, propene (C3H6) was used as a model compound for hydrocarbon oxidation, 174 following common practice [5,10,11,23,24,46]. The propene conversion was determined based on the CO2 175 concentrations measured in the product gas, using the same analyzer as for CO oxidation, and the 176 stoichiometry of the reaction equation, forming three CO2 molecules per C3H6 molecule.…”
Section: / 41mentioning
confidence: 99%
“…As a means of reducing CH 4 emissions, a major challenge for the environment, the total catalytic oxidation of CH 4 has been extensively studied [27][28][29][30][31]. The complete oxidation of CH 4 into CO 2 (a less potent greenhouse gas), particularly at low temperatures (below 500 • C), has been widely studied [32][33][34].…”
Section: Introductionmentioning
confidence: 99%